THE HADITH OF THE NIGHT PRAYER, MUTHANNA, MUTHANNA BY ABU MUHAMMAD TAQI AL-DIN AHMAD BIN ALI AL-MAQRIZI, WHO DIED IN THE YEAR (485 AH), A STUDY AND VERIFICATION - MAHMOUD , MOHAMED (Islamic Sciences Journal, 2023)
Prayer is the link of the human to his Lord, is the only obligatory imposed by Allah on the Prophet peace be upon him without intermediary, and the Sunnah which is non-obligatory prayers performed by the Muslim to be closer to Allah, and one of the best prayers to make the Muslim closer to Allah is the night prayer as it came in many verses and Ahadith (The prophet speeches). In this paper, Imam al-Maqrizi discusses Hadeeth (The speech ) of the Prophet (peace and blessings of Allah be upon him) about the night and day prayers not obligatory and how they performed. Is it performed dual or quadruple ? He mentioned the hadith narratives and its evidences in that, and went on to say that the Sunnah prayed dual at night and day, and the reason for the writing of this research was the discussion with the jurist Hanafi, whose name was not mentioned, but described it as not familiar with the branches of sect as mentioned at the beginning of the research.